Hierarchy and diffusion of organizational forms - Fioretti, Guido; Neumann, Martin (Frontiers in Psychology, 2022)
In this paper we summarize and rationalize current typologies of organizations and organizational forms, highlighting the importance of organizational routines and behavior patterns. We arranged these organizational forms in a hierarchy of increasing generality, and we gathered available knowledge on their birth and diffusion. In particular, we analyzed the structures of information flows that were operating during diffusion processes highlighting a secular trend towards greater information centralization and greater speed of diffusion.